Future effectual role of energy delivery: A comprehensive review of Internet of Things and smart grid. (August 2018) - Reka, S. Sofana; Dragicevic, Tomislav
Abstract: In today's ecosystem of energy management, the contribution of Internet of Things (IoT) to smart grids has acquired immense potential due to its multi-faceted advantages in various fields. IoT paves a way to associate and virtually control everything in almost every domain of society. Conversely, the smart grid framework attracted the attention of the universal research community and the idea of merging IoT with smart grid together demonstrates enormous growth potential. This review paper highlights the most significant research works that focus on applying IoT to smart grids. This work also addresses many innovative approaches used in IoT and smart grids along with their respective applications in various fields. The objective of this work is to benefit scientists and new entrants in the field of IoT and smart grids opens up awareness for new interdisciplinary research. Highlights: This review paper highlights the most significant research works that focus on applying IoT to smart grids. The objective of this work is to benefit scientists and new entrants in the field of IoT and smart grids opens up awareness for new interdisciplinary research. This paper portrays an exemplary candidate that offers myriad possibilities on the futuristic technology on energy consumption and utilization in a dystopian society.